The Relationship Between Auditory Memory Digit And Receptive Language Ability Of Preschool Age Child In Surakarta - Muryanti Muryanti; Windiarti Dwi Purnaningrum (Interest : Jurnal Ilmu Kesehatan, 2022)
Background: Receptive language is the ability to understand what is seen and heard to help children develop listening skills, identify concepts through understanding the labeling of words, and improve the ability to respond to any communication. Auditory memory involves the ability to retrieve information presented orally. This study analyzed the relationship between auditory memory digit and preschool-age child receptive language ability. Methods: This study was quantitative research. The research design used in this study was an observational correlation with a cross-sectional approach. The research sample consisted of 58 students in three Private Kindergartens existing in the Ministry of Education and Culture of Surakarta. Auditory memory testability of sample using hearing forward test and receptive language ability of sample using Assessment of Children's Language Comprehension form. Hypothesis testing using the Chi-Square hypothesis. Results: The result it can be concluded that auditory memory digit does not have a relationship with receptive language ability in preschool-age children because significance value more than 0.05 (ρ>0.05) with an OR value of 0.857, this means that the auditory memory digit is above average has a meager chance of influencing receptive language ability above average, which is only 0.857. Conclusion: The dominant factor influencing the receptive language skills of children aged 3-6 years is communication during interactions or activities with parents, such as reading fairy tales or telling stories. Receptive language skills predicted symbolic understanding as reflected in picture comprehension and how language skills are interrelated with social skills.